Continuance usage intention model of physical activity tracking technology - Wanichavorapong, Nittee (2019)
In eHealth, physical activity (PA) tracking technology exists that can assist people in monitoring their PAs. However, long-term use is the cornerstone of information technology (IT) product and service success; otherwise, it is a failure. Then, persistence becomes a factor of concern and it fades away over time. There is limited knowledge of information system (IS) continuance in this domain called PA tracking devices and apps (PATDA). Prior IS continuance research has no suitable models that can explain continuance intention (CI) of PATDA. The aim of this study is to build a model that predicts users to continue using PATDAs. This study also demonstrated the use of expectation-confirmation model (ECM), Network externalities (NE), and Value-based factors to understand CI of PATDA. Through data collection, a survey method was carried out among PATDA Singaporean users. The proposed model has been tested for reliability and validity using a Structural Equation Modelling (SEM) method. The results exhibited that all the ECM constructs had statistically significant impacts on CI. However, Social Value (SS) had rather an insignificant correlation with CI. Referent Network Size (RNS) also received an insignificant association with Usefulness. Besides, the analysis showed many of the constructs clustered in the group that yielded high performance and importance, including Satisfaction, Utilitarian, Confirmation, Hedonic, Complementarity, and Usefulness. Referent Network Size arrived in the middle between Social Value, which is rated as insufficient on performance and importance and the outstanding group. The research model can be functioning as a guideline to increase the understanding regarding the CI of a PATDA. By applying the evaluation result of identified factors, stakeholders can embrace a range of benefits from PA tracking technology in connection with research, product features, and usage.